Teologi Paulus Tentang Penderitaan: Suatu Analisis Terhadap 2 Korintus 1:3-11 - Noor Anggraito; Linus Elabi (Sekolah Tinggi Teologi Bethel Ambon, 2023)
The suffering theology is not an interesting topic of discussion in the Christian ministry. However, Christians must realize that suffering in the ministry is an unavoidable event. Jesus became the typology of suffering for Christians. Although the theology of suffering is often voiced in various spaces such as sermons, mission oration or in seminary classes, the facts show that Christians will avoid suffering caused by challenges in Christian ministry. This paper describes Paul's perspective on the suffering he experienced in the ministry he did. Through the method of biblical analysis it has been found that suffering is the price to be paid for the gospel being proclaimed.